APPLICATION OF THE JITUPASNA MODEL IN POST-FLOOD HEALTH CRISIS SURVEILLANCE - Subandi, Andi; Amalya Nasution, Riska; Oktarina, Yosi; Noerjoedianto, Dwi (Universitas Aisyah Pringsewu, 2024)
Flood-induced health crises are one of the major problems impacting the public health sector, especially in disaster-prone areas such as Bungo District, Jambi Province. Floods often result in the spread of infectious diseases, poor sanitation, and psychological stress, so there is a need for effective health surveillance. This study aimed to evaluate the application of the JITUPASNA model in post-disaster health crisis surveillance in flood-prone areas. This quasi-experimental study used a pre-test and post-test design on two groups with a total of 57 respondents, consisting of health surveillance officers from local health centers and the Health Office. Data was collected using a questionnaire that measured the respondents' knowledge level before and after the intervention. The results of the analysis showed a significant increase in respondents' knowledge, with 100% reaching a high level of knowledge in the second post-test phase. The JITUPASNA model had a significant impact on health surveillance knowledge, enabling faster and more accurate responses in post-disaster health crises. These findings underscore the potential of JITUPASNA to improve health surveillance systems, especially in disaster-prone areas where rapid response is critical.